(untitled) (Agroindustrial Science, 2021)
The aim of the work was to evaluate the biostimulant effect of plant extracts of Cleome viscosa L. on the in vitro germination of two varieties of pepper (Capsicum annuum L.). A bioassay was set up on a completely randomized design with a control and 18 treatments with three samples each, evaluating the effect on the dynamics and percentage of germination, radicle length and hypocotyl length. The chemical families present in the extracts were determined by phytochemical characterization. For the length of the radicle and the hypocotyl, the extracts with the best potentialities in the Verano 1 variety are those obtained from the root and stem, although the concentrations with the best influence on both indicators are 1 and 3 of the root extracts. Differences in the richness of chemical families were verified in the extracts with the best results, although the best composition was obtained in those of the root and stem, showing the presence of free amino acids in all cases. Cleome viscosa is promising for obtaining products with a biostimulant effect on the varieties of pepper studied, obtaining a better effect when root, stem and whole plant extracts are applied.